Mike and Mike's rules for sports and life - Greenberg, Mike, 1967-; Golic, Mike.; Chaikivsky, Andrew; ESPN (Television network) (New York : ESPN Books, 2010)
The ESPN comedy team presents an offbeat list of sports rules to live by, in a treasury of provocative ideas and proclamations culled from their top-rated morning show.
Rule 1.28. Baseball managers should dress like normal people -- Rule 2.96. One day, athletes will rule the world -- Rule 3.49. Fans are crazy because people are crazy -- Rule 4.01. The most philosophical of all sports? College football! -- Rule 5.36. A house without a baseball glove is not a home.
Keywords: Sports -- Humor; Sports -- Rules -- Humor; Sports -- Humor; Sports -- Miscellanea